P100 Wave Latency and Amplitude in Visual Evoked Potential Records in Different Visual Quadrants of Normal Individuals - Leila Mirzaee Saba; Hassan Hashemi; Ebrahim Jafarzadehpour; Ali Mirzajani; Abbasali Yekta; Abolfazl Jafarzadehpour; Arghavan Zarei; Payam Nabovati; Mehdi Khabazkhoob (Journal of Ophthalmic & Vision Research, 2023)
Abstract Purpose: Assessment of the pattern visual evoked potential (PVEP) responses in different areas of visual fields in individuals with normal vision. Methods: This study was conducted on 80 eyes of normal subjects aged 18–35 years. All participants underwent refraction and visual acuity examination. Visual evoked potential (VEP) responses were recorded in different areas of field. The repeated measure test was used to compare the P100 latency and amplitude of PVEP among different areas. Results: The repeated measures analysis of variance showed a statistically significant difference among different areas in terms of amplitude and latency of P100 (P = 0.002 and P < 0.001, respectively). According to the results, the highest and lowest amplitude of P100 was observed in inferior-nasal and superior areas, respectively. The highest and lowest latency of P100 was related to the temporal and inferior-nasal areas, respectively. Conclusion: This study partially revealed the details of local PVEP distribution in the visual field and there was a significant difference in the amplitude and latency of PVEP wave in different areas of the visual field.